Implementasi Pendekatan Deep Learning Dalam Pembelajaran Drama Pada Kelas XI - Lintang Rona Kamila; Andayani Andayani (JURNAL MANAJEMEN PENDIDIKAN, 2026)
THE IMPLEMENTATION OF THE DEEP LEARNING APPROACH IN DRAMA LEARNING FOR GRADE XI STUDENTS The deep learning approach is an educational transformation emphasised by the Ministry of Education and Culture. This study aims to describe (1) the planning of drama lessons using a deep learning approach in Year 11, (2) the implementation of drama lessons using a deep learning approach, and (3) the challenges faced by teachers and their solutions in implementing drama lessons using a deep learning approach. This study employs a qualitative approach using a case study strategy. The data sources for this study were drawn from Deep Learning Lesson Plans (RPM), events that occurred during the implementation of the lessons, and informants comprising Indonesian language teachers and Year 11 students. Sampling was carried out using purposive sampling. Data collection was carried out by analysing RPM data, conducting non-participant observation, and in-depth interviews. The data validity test technique used was source and method triangulation. Data analysis was carried out using an interactive model. The findings of this study are as follows: (1) teachers’ lesson planning involves analysing the suitability of teaching materials to pupils’ abilities and designing lesson plans that incorporate the four main aspects but do not yet meet the requirements for a complete document; (2) the delivery of lessons does not yet comply with lesson planning procedures, but does incorporate the three principles and learning experiences; (3) the challenges faced by teachers include time constraints, limited facilities and infrastructure, and the use of technology, which were addressed by collaborating with History teachers, arranging the time and venue for the drama performance, and providing access to online assessment.